Intraepithelial lymphocytes subsets in Crohn’s disease patients - Mohammad, Ali J.; Nizheharodava, Darya B.; Varabei, Alexander V.; Starastsin, Andrey M.; Zafranskaya, Marina M. (Journal of the Belarusian State University. Ecology, 2022)
Crohn’s disease is an autoimmune inflammatory bowel disease characterized with the chronic relapsing-remitting inflammation, mainly in the terminal parts of the small intestine and colon, as a result of a genetic predisposition or environmental factors influence. It is associated with impaired bacterial clearance and changes in immunological parameters what resulted in disruption of the gastrointestinal tract ecosystem, formed by the microbiome and non-living components such as mucus, food metabolites or additives. Intraepithelial lymphocytes of the gastrointestinal tract play an important role in mucosal immunity and their phenotype and functional profile is largely determined by the microbiome composition and environmental factors affecting it (diet, smoking, seasonal changes, air pollution, hygiene, etc.). In this investigation the changes in intraepithelial lymphocytes phenotype of small and large intestine were shown in patient with Crohn’s disease as well as the correlation of intraepithelial lymphocytes phenotype with clinical data was established. Obtained data may be used as a hallmark of immune inflammation in the gut and make intraepithelial lymphocytes as ideal candidate for targeting in further immunoregulation of mucosal adaptive immune response against autoantigens.